Pre- and Postoperative Photographs and Surgical Outcomes in Patients With Lenke Type 1 Adolescent Idiopathic Scoliosis. Issue 7 (1st April 2015) - Albayrak, Akif; Buyuk, Abdul Fettah; Ucpunar, Hanifi; Balioglu, Mehmet Bulent; Kargin, Deniz; Kaygusuz, Mehmet Akif
<x xml:space="preserve">Abstract</x> Study Design. Clinical study with pre- and postoperative back photographs and postoperative Scoliosis Research Society-22 survey in patients who had undergone surgery for idiopathic scoliosis. Objective. To determine the effect of showing patients their photographs before and after surgery for idiopathic scoliosis on postoperative patient satisfaction. Summary of Background Data. After scoliosis surgery, patient satisfaction may be limited because the patients cannot directly see their back and may forget the preoperative appearance. Methods. In 60 patients who had undergone surgery for correction of idiopathic scoliosis (Lenke type 1), pre- and postoperative photographs were taken from the anterior, posterior, and right and left lateral views. After surgery, patients in group 1 (30 patients) were shown the preoperative and most recent follow-up photographs, and patients in group 2 (30 patients) had routine evaluation but were not shown their photographs. All patients completed the Scoliosis Research Society-22 survey. Results. Patients in both groups had similar age, sex, distribution of Lenke type and Risser sign, follow-up, and pre- and postoperative Cobb angles and balance (coronal and sagittal). A significant difference was observed between the groups for survey question 10 (which was about self-image), question 18 (which was about function and activity), and question 21 (which was about satisfaction) (P ⩽ 0.05). There were no differences between patients in groups 1 and 2 in Scoliosis Research Society-22 domain or total scores. Conclusion. By showing patients the pre- and postoperative clinical photographs, patient satisfaction may be greater, as measured with some SRS-22 scores. This method may enable clinicians to positively change the patients' self-image perception after surgery for correction of scoliosis. Level of Evidence: 4